Experimental investigation of the effects of the coverage of helical strakes on the vortex-induced vibration response of a flexible riser. (September 2016) - Gao, Yun; Yang, Jiadong; Xiong, Youming; Wang, Menghao; Peng, Geng
Highlights: We studied the standing wave behavior as well as travelling wave behavior of a flexible riser in both uniform and linearly sheared currents. We studied the VIV response of a flexible riser with different strakes coverages in both uniform and linearly sheared currents. We further discussed the comprehensive evaluation of a flexible riser with different strakes coverages. Abstract: The effects of different helical strake coverage on the vortex-induced vibration (VIV) of a model flexible riser were studied experimentally, with the aim of further improving the understanding of VIV responses. Uniform and linearly sheared currents were simulated to study response parameters such as non-dimensional displacement, fatigue damage, suppression efficiency, and the comprehensive evaluation is further studied. Test results of the bare model for a uniform current showed that the behavior of both the standing wave and traveling wave dominated VIV displacement. However, for a linearly sheared current, traveling wave behavior dominated VIV displacement in the high-velocity range. The results of the straked model tests indicated that the response was strongly dependent upon the amount of coverage of helical strakes. The flexible riser with 75% strake coverage gave the best comprehensive evaluation in a uniform current, and 50% strake coverage gave the best comprehensive evaluation in a linearly sheared current.